2010
DOI: 10.1177/009164711003800205
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and Faith Development

Abstract: Recent research has shown the relationship between an attachment to caregivers and an attachment to God, an attachment to God and adult attachment, attachment to God and religiosity, and attachment and spiritual maturity, but has failed to examine the link between attachment and faith development (which includes not only the relational but also the imaginative nature in the questioning and answering process regarding philosophical notions of existence). The current project investigated the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Insecure attachment means that it does not produce sustainable positive emotions and strong emotional regulation and thus may result in personality disorders (Ghobary Bonab et al 2013). Research by Hart et al (2010) revealed that faith development is predicted by attachment anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Insecure attachment means that it does not produce sustainable positive emotions and strong emotional regulation and thus may result in personality disorders (Ghobary Bonab et al 2013). Research by Hart et al (2010) revealed that faith development is predicted by attachment anxiety.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Main and Solomon (1986;1990) later identified the disorganised attachment style, a fourth pattern, in which infants seemed disoriented and confused about attachment-seeking, as they exhibited tendencies of both anxious and avoidant styles (cf. Hart, Limke, Budd 2010). Regardless of the style, Bowlby's attachment theory was developed to elucidate the kernels of truth in Freud's insights about close relationships by replacing his image of a needy, dependent infant motivated by drive reduction with one of a sophisticated, competence-motivated infant using its primary caregiver as a secure base from which to explore and, when necessary, as a haven of safety and a source of comfort (Waters & Cummings 2000:165).…”
Section: Attachment Theory and The Search For A Religious Attachment mentioning
confidence: 99%
“…A study by Hart, Limke, and Budd () suggested that an individual's stage of faith development based on Fowler's () model might be related to his or her level of attachment anxiety. In Fowler's view (as cited in Hart et al, ), people heighten their stage of faith development by forming increasingly complex and comprehensive belief structures: People with insecure attachment (and a low level of faith development) may adhere to religious dogma in an effort to avoid the anxiety of uncertainty and doubt, whereas people of faith with secure attachment believe that God will look after them regardless of their circumstances, which greatly reduces abandonment anxiety. Hart et al () found that, for many undergraduate students, “attachment to caregivers [was] reenacted in attachment to God” (p. 122).…”
Section: Prayer Faith Development and Religious Copingmentioning
confidence: 99%